Traditional Chinese medicine: An important source for discovering candidate agents against hepatic fibrosis - Li, Wen-Qing; Liu, Wen-Hao; Qian, Die; Liu, Jia; Zhou, Shi-Qiong; Zhang, Lei; Peng, Wei; Su, Li; Zhang, Hong (Frontiers in Pharmacology, 2022)
ABSTRACT Context: Hepatic fibrosis (HF) refers to the pathophysiological process of connective tissue dysplasia in the liver caused by various pathogenic factors. Nowadays, HF is becoming a severe threat to the health of human being. However, the drugs available for treating HF are limited. Currently, increasing natural agents derived from traditional Chinese medicines (TCMs) have been found to be beneficial for HF. Objective: This paper was designed to review the potential TCMs for treating HF. Methods: A systemic literature search was conducted from PubMed, GeenMedical, Sci-Hub, CNKI, Google Scholar and Baidu Scholar, with the keywords of “traditional Chinese medicine”, “herbal medicine”, “natural agents”, “liver diseases” and “hepatic fibrosis”. Literatures are mainly from Jan. 2007 to Mar. 2022 with no limitation for language. Results: So far, more than 76 natural monomers have been isolated and identified from the TCMs with inhibitory effect on HF, including alkaloids, flavones, quinones, terpenoids, saponins, phenylpropanoids, and polysaccharides, etc. The anti-HF effects of these compounds include hepatoprotection, inhibition of hepatic stellate cells (HSC) activation, regulation of extracellular matrix (ECM) synthesis & secretion, and antioxidant & anti-inflammation, etc. Conclusions: Natural compounds and extracts from TCMs are promising agents for the prevention and treatment of HF, and this review would be of great significance to development of novel drugs for treating HF.